Social Organization of the Mongolian Nomad Community in XXI Century: Role of Family Ties - A. D. Gombozhapov (Научный диалог, 2021)
The issues of kinship in the social self-organization of nomads are considered. The results of field studies in various regions of Mongolia, which unambiguously record the existence of informal family-related groups, united on the basis of, first of all, common economic and household interests are presented. The author notes the functions of the nomadic community: law enforcement, expressed in the collective protection of pasture lands and their joint ownership; cooperative, involving labor cooperation, mainly of a seasonal nature, and spiritual, associated both with the holding of common religious, festive and other events, and with the regulation of conflict relations within the nomadic community on the basis of traditional moral values. It is shown that contradictions in the legal issues of the use of pasture lands, on the one hand, and the temporality and relativity of the territorial settlement inherent in the nomadic way of life, on the other, contribute to the stable existence of the nomadic community. It is concluded that socio-legal regulation in the absence of effective public-state institutions is replaced by traditional ideas about property rights, the carriers of which are represented by family-related groups of nomads. It is emphasized that the role of kinship as a characteristic social resource is also manifested in migration processes in Mongolian society.